2019
DOI: 10.3389/fpsyg.2019.01592
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results From a Randomized Controlled Study for an App-Based Cognitive Behavioral Therapy Program for Depression and Anxiety in Cancer Patients

Abstract: Cancer patients experience various psychological and social difficulties, the most common being depression and anxiety. The purpose of this study was to develop and evaluate the effectiveness of an app-based cognitive behavioral therapy program for depression and anxiety in cancer patients. For this purpose, 63 participants who met the inclusion criteria were randomly assigned to either a mobile-application-based cognitive behavioral therapy program (HARUToday), a simple information-provision mobile-applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
67
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(82 citation statements)
references
References 86 publications
1
67
0
1
Order By: Relevance
“…In women with incurable cancer and with elevated anxiety symptoms, a tablet-delivered CBT program (intervention) and health education program (control group) delivered via tablet computers were associated with a significant improvement in the FACT-General questionnaire scores, yet without a statistically significant between-group differences ( Greer et al, 2019 ). Ham and colleagues found a similar between-group improvement of the SF-36 total score in cancer patients randomized to either a mobile-application-based CBT ( HARUToday ), a waitlist control group, or an attention control group ( Ham et al, 2019 ). Another RCT found that cancer patients randomized to either an Internet-based mindfulness-based cognitive therapy or a face-to-face mindfulness based cognitive therapy had improved mental health, but not physical health, when compared to cancer patients who received treatment as usual ( Compen et al, 2018 ).…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…In women with incurable cancer and with elevated anxiety symptoms, a tablet-delivered CBT program (intervention) and health education program (control group) delivered via tablet computers were associated with a significant improvement in the FACT-General questionnaire scores, yet without a statistically significant between-group differences ( Greer et al, 2019 ). Ham and colleagues found a similar between-group improvement of the SF-36 total score in cancer patients randomized to either a mobile-application-based CBT ( HARUToday ), a waitlist control group, or an attention control group ( Ham et al, 2019 ). Another RCT found that cancer patients randomized to either an Internet-based mindfulness-based cognitive therapy or a face-to-face mindfulness based cognitive therapy had improved mental health, but not physical health, when compared to cancer patients who received treatment as usual ( Compen et al, 2018 ).…”
Section: Resultsmentioning
confidence: 81%
“… ( Park et al, 2019 ) Republic of Korea Lung cancer 90 / 54% women / 55.1 ± 8.7 years Pre-post App delivered physical rehabilitation program (Smart Aftercare app) None 12 weeks EORTC QLQ-C30 90% Improved role, emotional and social functioning, fatigue, appetite, diarrhea ( Trinh et al, 2018 ) Canada Prostate cancer 46 / all men / 73.2 ± 7.3 years Pre-post Accelerometer, wrist-worn activity tracker and Web based application None 12 weeks FACT-General 91% Improved emotional well-being ( Lozano-Lozano et al, 2019 ) Spain Breast cancer (Overweight/obese) 80 / all women / age 59 ± 9 years Pre-post Healthy eating and physical activity feedback app (BENECA) None 8 weeks EORT QLQ-C30 73% Improved global health, physical, emotional, social and cognitive functioning, fatigue, dyspnea, insomnia Cognitive behavioral therapy / behavioral change (6 studies) ( Greer et al, 2019 ) USA Incurable cancer (patients with high anxiety) 145 / 74% women / mean age: 56 ± 11 years RCT CBT (tablet based) Health education program 12 weeks FACT-G - QOL improved in both patient groups. ( Ham et al, 2019 ) South Korea Different cancer types …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All trials consisted of individually RCTs. In all, 25 % (3/12) of the trials included people with mild to moderate depression [ 34 , 39 , 41 ], 17% (2/12) of the trials included people with mild to severe depression [ 33 , 40 ], 42% (5/12) of the trials included people with moderate to severe depression [ 35 , 36 , 42 - 44 ], 8% (1/12) of the trials included people with a diagnosis of major depression [ 38 ], and 8% (1/12) of the trials included people with a self-reported need for help with their depressive symptoms [ 37 ]. The total combined sample size for all included trials was 2859 participants.…”
Section: Resultsmentioning
confidence: 99%
“…Ainda sobre a ansiedade, os estudos realizados porAubin et al (2019) eHam et al (2019) obtiveram dados significativos em relação ao uso da TCC em formato on-line, por meio de aplicativos mĂłveis, com melhora em relação Ă  ansiedade nos grupos da intervenção.Em se tratando da questĂŁo da depressĂŁo, constatou-se que o estudo deGreer et al (2012) apresenta contribuiçÔes considerĂĄveis na redução dos sintomas depressivos, da mesma forma que os estudos de MejĂ­a-CastrejĂłn e Landra-RamĂ­rez (2014) eHam et al (2019) demonstram que a TCC foi Ăștil na redução da depressĂŁo. Um dado interessante sobre o estudo deHam et al (2019) Ă© que os achados foram coletados em uma grande variedade de estĂĄgios e tipos de cĂąncer.…”
unclassified